The Influence of Value Co-Creation and Mastery of Technology on Operational Performance Through Employee Performance - Rinandiyana, Lucky Radi; Budiman, Asep; Kurniawan, Dian; Badriatin, Tine (Almana : Jurnal Manajemen dan Bisnis, 2023)
The application of value co-creation and mastery of information technology is fundamental to creating employee performance which will ultimately influence the company's operational performance. From this phenomenon, the question that will be answered in this research is how value co-creation and mastery of information technology influence the operational performance of coffee shop company employees in Tasikmalaya with employee performance as a mediating variable. The purpose of this research is to determine and analyze the effect of implementing value co-creation on employee performance in coffeeshops, the use of information technology on employee performance in coffeeshops, value co-creation and the use of information technology on employee performance and employee performance mediates the influence of implementing value co-creation and the use of information technology on operational performance. The method used was a survey with a population of 322 which was processed using confirmatory factor analysis (CFA) with the AMOS 21 program. The research results showed that there was an influence between Value Co-Creation on Employee Performance, Information Technology on Employee Performance, Employee Performance on Operational Performance, Performance Employees mediate the relationship between Value Co-Creation and Operational Performance, and Employee Performance mediates the relationship between Information Technology and Operational Performance.